Developing collaborative marine turtle monitoring in the Kimberley region of northern Australia. (15th September 2015) - Jackson, Micha V.; Kennett, Rod; Bayliss, Peter; Warren, Robert; Waina, Neil; Adams, Jason; Cheinmora, Leonie; Vigilante, Tom; Jungine, Edmund; Woolagoodja, Kirk; Woolagoodja, Francis; Umbagai, Jermaine; et al.
Abstract : Contemporary land and sea management – driven by community‐based planning and informed by traditional and local knowledge and scientific research – can significantly improve both biodiversity and cultural outcomes. Here, we describe the context and process of developing a boat‐based survey approach to marine turtle monitoring by Indigenous rangers using a collaborative partnership model that supports Traditional Owner aspirations and conservation objectives.